Penerapan Hukuman Mati bagi Pelaku Tindak Pidana Korupsi - Sawfa Fiznnah; Siti Aulia Zahro; Nazwa Yonda Syahvira; Habibah Hasanah Ali (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Corruption is an extraordinary crime that has significant impacts on economic conditions, social life, and public trust in the legal system. One of the efforts to combat corruption in Indonesia is the regulation of the death penalty under the Corruption Eradication Law, particularly Article 2 paragraph (2), which allows its application under “certain circumstances.” This study aims to examine the concept of corruption, the development of its legal regulation in Indonesia, and the implementation of the death penalty from juridical, sociological, and practical perspectives. The research employs a normative juridical method with a descriptive-analytical approach supported by literature studies of legislation, books, and scientific journals. Data were analyzed qualitatively to obtain a comprehensive understanding of the issue. The findings indicate that the death penalty has been legally regulated as the most severe sanction for corruption offenders. However, despite its legal basis, the sanction has never been applied in practice. This situation is influenced by the ambiguity of the term “certain circumstances,” human rights considerations, and institutional challenges in law enforcement, including the dynamics of the role of the Corruption Eradication Commission (KPK). In addition, law enforcement authorities tend to exercise caution and often prefer alternative charges to avoid legal and social controversy. Therefore, clearer legal norms, consistent law enforcement, and stronger institutional commitment are necessary to ensure the effectiveness of corruption eradication policies.